Pelatihan Literasi Digital dalm Pembelajaran Mendalam Menggunakan Edu Game Terintegrasi Budaya Lokal bagi Guru di Provinsi Lampung - Rahayu, Chika; Sutiarso, Sugeng; Prastyo, Yanuar Dwi; Surawan, Ghea Chandra (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service program aims to enhance teachers’ understanding and competence in digital literacy by developing research-based educational games that integrate local wisdom and have a sustainable impact on deep learning. The implementation methods used were training and mentoring activities. The target partners of this program were teachers from SDN Mulyo Haji, Anak Tuha District, Lampung Province. The evaluation technique employed was the CIPP model (Context, Input, Process, and Product). The results of this community service activity show an improvement in teachers’ understanding and competence in digital literacy, as evidenced by an average score of 90.77 (maximum 100 and minimum 60). In addition, teachers were able to design lesson plan products and educational games that are ready for classroom implementation.